PENYEBARAN HAMA BARU PADA TANAMAN PEPAYA DAN PAKIS HAJI DI SULAWESI UTARA DISTRIBUTION AND STATUS OF NEWLY INTRODUCED INSECT PESTS OF PAKIS HAJI IN NORTH SULAWESI - Sembel, Dantje T.; Meray, Elisabeth R.M.; Kandowangko, Daisy S.; Dien, Moulwy F.; Ratulangi, Max M. (EUGENIA, 2012)
ABSTRACTThe objective of this work was to study the distribution and state of the new and accidentally introducedinsect pests of papaya and pakis haji in North Sulawesi. Results showed that the papaya mealy bug,Paracoccus marginatus (Hemiptera: Pseudococcidae) has spread and establised in North Sulawesi butits level of infestation has been from low to medium depending on the location. The main naturalenemies found on the papaya mealy bug were Coccinelidae (Coleoptera), Hermetia illucens (Diptera:Stratiomyidae) and Acerophagus papaya (Hymenoptera: Encyrtidae). The Cycad scale, Aulacaspisyasumatsui Takagi (Hemiptera: Diaspididae) and yellow beetle, Lilioceris sp. (Coleoptera:Chrysomelidae) were first recorded on pakis haji in North Sulawesi and causing damage to pakis haji inthis region. The predator found on cycad scale was a beetle, of the famili Cybocephalidae genusCybocephalus.Keywords: Paracoccus marginatus, Aulacaspis yasumatsui, Lilioceris sp, papaya and pakis haji